Mastering Puppet 5 : optimize enterprise-grade environment performance with Puppet - Russell-Yates, Ryan; Southgate, Jason (Packt Publishing, 2018)
Leverage Puppet 5 for medium to large scale enterprise deployment. Key Features Use and deploy Puppet 5, irrespective the size of your organization Scaling, performance improvements, and managing multiple developer requests Troubleshooting techniques, tips and tricks to make the most of Puppet 5 Book Description Puppet is a configuration management system and a language written for and by system administrators to manage a large number of systems efficiently and prevent configuration drift. The core topics this book addresses are Puppet's latest features and mastering Puppet Enterprise. You will begin by writing a new Puppet module, gaining an understanding of the guidelines and style of the Puppet community. Following on from this, you will take advantage of the roles and profiles pattern, and you will learn how to structure your code. Next, you will learn how to extend Puppet and write custom facts, functions, types, and providers in Ruby, and also use the new features of Hiera 5. You will also learn how to configure the new Code Manager component, and how to ensure code is automatically deployed to (multiple) Puppet servers. Next, you will learn how to integrate Puppet with Jenkins and Git to build an effective workflow for multiple teams, and use the new Puppet Tasks feature and the latest Puppet Orchestrator language extensions. Finally, you will learn how to scale and troubleshoot Puppet. By the end of the book, you will be able to deal with problems of scale and exceptions in your code, automate workflows, and support multiple developers working simultaneously. What you will learn Solve problems using modules and the roles and profiles pattern Extend Puppet with custom facts, functions, types, and providers Use Hiera 5 and Code Manager/r10k to separate code from data Continuously integrate your code using Jenkins, Git and automated testing Use exported resources and the new Puppet Orchestration features Explore Puppet Discovery features and their use Troubleshoot various parts of the Puppet Enterprise infrastructure Scale up and scale out Puppet infrastructure using various techniques Who this book is for If you are a system administrator or developer who has used Puppet in production and are looking for ways to easily use Puppet in an enterprise environment, this book is for you. Some knowledge of writing simple configuration management modules would be necessary.